A deeply divergent phosphoglucomutase (PGM) of Giardia lamblia has both PGM and phosphomannomutase activities - Mitra, Sanghamitra (Oxford University Press, 2010)
Giardia lamblia, which is an important parasitic cause of diarrhea, uses activated forms of glucose to make glycogen and activated forms of mannose to make glycophosphosphoinositol anchors. A necessary step for glucose activation is isomerization of glucose-6-phosphate to glucose-1-phosphate by a phosphoglucomutase (PGM). Similarly, a phosphomannomutase (PMM) converts mannose-6-phosphate to mannose-1-phosphate. While whole genome sequences of Giardia predict two PGM candidates, no PMM candidate is present. The hypothesis tested here is that at least one of the two Giardia PGM candidates has both PGM and PMM activity, as has been described for bacterial PGM orthologs. Nondenaturing gels showed that Giardia has two proteins with PGM activity, one of which also has PMM activity. Phylogenetic analyses showed that one of the two Giardia PGM candidates (Gl-PGM1) shares recent common ancestry with other eukaryotic PGMs, while the other Giardia PGM candidate (Gl-PGM2) is deeply divergent. Both Gl-PGM1 and Gl-PGM2 rescue a Saccharomyces cerevisiae pgm1Δ/pgm2Δ double deletion strain, while only Gl-PGM2 rescues a temperature-sensitive PMM mutant of S. cerevisiae (sec53-ts). Recombinant Gl-PGM1 has PGM activity only, whereas Gl-PGM2 has both PGM and PMM activities. We conclude that Gl-PGM1 behaves as a conventional eukaryotic PGM, while Gl-PGM2 is a novel eukaryotic PGM that also has PMM activity.